(untitled) (Biological Sciences - PJSIR, 2000)
This study comprised physico-chemical analysis of selected fertilizer effluent, evaluation of hazardous pollutants, their effects on crop plants and remedial measures.Effluent samplesof selectedphosphatic and nitrogenous fertilizer industrieswerecollected,periodically.The sampleswereanalysedforpH,conductivity,hardness,alkalinity,dissolved solids, suspended solids, chemical oxygen demand (COD), chlorides, sulphates, sulphides, phosphates, silica, chlo- rine, ammonia, calcium, magnesium and iron. Trace metals like arsenic, cadmium, chromium, cobalt, copper, lead, manganese, nickel, tin and zinc were also checked. Effects of these effluents on crop plants and vegetables were observed and remedial measures for the hazardous pollutants of these effluents suggested.